1991
DOI: 10.1101/gad.5.4.561
|View full text |Cite
|
Sign up to set email alerts
|

Glucose repression of transcription of the Schizosaccharomyces pombe fbp1 gene occurs by a cAMP signaling pathway.

Abstract: Transcription of the fbpl gene, encoding fructose-l,6-bisphosphatase, of Schizosaccharomyces pombe is subject to glucose repression. Previous work has demonstrated that several genes {g/t genes} are required for this repression. In this report we demonstrate that one of these genes, git2, is the same as the cyrl gene, which encodes adenylate cyclase, and that loss-of-function mutations in git2 cause constitutive fbpl transcription. Addition of cAMP to the growth medium suppresses the transcriptional defect in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
144
2
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(153 citation statements)
references
References 61 publications
6
144
2
1
Order By: Relevance
“…Furthermore, as shown in Figure 3D, the Gad8 phosphorylation was not induced in glucose-starved cells after being treated with 5 mM cAMP, which is known to activate PKA in S. pombe. 40 It is therefore unlikely that the cAMP-PKA pathway mediates glucose signals to control the TORC2 activity. Gad8 is immediately dephosphorylated upon glucose depletion in the growth medium.…”
Section: Glucose-regulation Of the Ryh1 Gtpase Contributes To Torc2 Amentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as shown in Figure 3D, the Gad8 phosphorylation was not induced in glucose-starved cells after being treated with 5 mM cAMP, which is known to activate PKA in S. pombe. 40 It is therefore unlikely that the cAMP-PKA pathway mediates glucose signals to control the TORC2 activity. Gad8 is immediately dephosphorylated upon glucose depletion in the growth medium.…”
Section: Glucose-regulation Of the Ryh1 Gtpase Contributes To Torc2 Amentioning
confidence: 99%
“…Our mutational analysis indicated that the glucose regulation of fission yeast TORC2 is not dependent on the cAMP pathway, a signaling mechanism known to be responsive to extracellular glucose. [39][40][41][42] Importantly, glucose-replete conditions increase the active, GTP-bound form of Ryh1 GTPase, which induces TORC2-dependent phosphorylation of Gad8. Glucose starvation swiftly inactivates Ryh1 and suppresses the TORC2-Gad8 pathway, which is, however, gradually reactivated in a manner independent of Ryh1.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of the S. pombe fbp1 gene, encoding fructose 1,6-bisphosphatase, was reported to be repressed in 8% glucose (36) because of regulation by a glucose-induced cAMP signal (37). The increased expression of mae2 observed in high concentrations of glucose (and therefore high cAMP levels) suggested that cAMP induction may be involved in this response.…”
Section: Discussionmentioning
confidence: 99%
“…This collection of mutants includes 31 strains carrying mutations in the git2 1 / cyr1 1 adenylate cyclase gene, some of which compose two intragenic complementation groups (Hoffman andWinston 1990, 1991). In vitro assays of adenylate cyclase activity showed wild-type catalytic activity in git2-7 and git2-210 strains from one group and reduced catalytic activity in a git2-61 strain from the second group (Hoffman and Winston 1991). Presumably, the first group is defective in a step involved in in vivo activation, such as binding an activator, while the second group is defective in catalytic activity.…”
Section: R176hmentioning
confidence: 99%
“…However, S. pombe Gpa2, which has recently been shown to directly bind an N-terminal domain of adenylate cyclase (Ivey and Hoffman 2005), functions together with the Git5-Git11 Gbg dimer (Landry et al 2000;Landry and Hoffman 2001), while the only authentic S. cerevisiae Gbg dimer, Ste4-Ste18, does not act in conjunction with Gpa2 (Liu et al 1993). In addition, Ras proteins play an important role in adenylate cyclase activation in S. cerevisiae, but have no role in the S. pombe cAMP pathway (Toda et al 1985;Fukui et al 1986;Mbonyi et al 1988;Hoffman and Winston 1991).…”
Section: R176hmentioning
confidence: 99%